REPRESENTATION OF THE EAST THROUGH THE WEST'S EYES : an Analysis of "Gardens of Water" by Alan Drew From Said's Perspective - MALIYANA, Yana (2012)
This research paper entitled Representaion of the East through the West's Eyes: The Analysis of Gardens of Water by Alan Drew from Said's Perspective is aimed to uncover the ways in which the western author, Alan Drew, represents non-Western culture in the novel. The research employs qualitative descriptive study with the content analysis approach. The analysis of the novel is done within the theoretical framework of Orientalism which is proposed by Edward Said (1978). The research proves that there are some traces of Orientalism that can be seen from the representation of the East on their attitudes, various events and setting, and their physical appearances. The results of the analysis show that the representation of non-western people and cultures confirms orientalist point of view that puts them in binary opposition and represents the East as inferior to the West. This construction of the East leads to the justification of the West imperialism toward the East.Keywords: Orientalism, the West, the East, the Orient, the Occident, representation,